Biofortificação agronômica de rúcula (Eruca sativa Miller.) com ferro em cultivo hidropônico - Ceccherini, Guilherme José (Universidade Federal de São Carlos, 2022)
Arugula is the second most cultivated leafy vegetable in the NFT (Nutrient Film Technique) hydroponic system, as it guarantees greater productivity, shorter cultivation cycle and greater efficiency in the use of water and fertilizers. Biofortification is a technique that aims to enrich the edible parts of agricultural products with micronutrients in the parts used for plant consumption. Biofortification, for example, with iron is a way to minimize anemia. The objective of this research was to evaluate the effect of iron doses on the biofortification of two arugula varieties in a hydroponic system, in the winter and summer period. The experimental design was in randomized blocks, with a factorial of 4 doses of chelated iron (EDDHA) (T1=1.8; T2=3.6; T3=5.4 and T4=7.2 g 1000L-1 ) x 2 arugula cultivars (V1= Astro and V2= Roka), with four replications. Agronomic evaluations of plant diameter, number of leaves, plant height, root length, root and shoot fresh mass, root and shoot dry mass, productivity and iron accumulation in shoots and roots were carried out, in addition to instrumental analysis of leaf area, total chlorophyll index and colorimetric analysis. Only the fresh root mass was equal to the statistics performed. Iron accumulation in roots was considerably higher than in leaf tissue, about 10-20 times higher. Therefore, in the winter period, Astro at the dose of 3.6 mg 1,000L-1 and Roka, in the summer period of the treatment, 7.2 mg 1,000L-1 , were the ones that showed the highest translocation and accumulation of Fe in the edible part.
Agronomic biofortification of arugula (Eruca sativa Miller.) with iron in hydroponic cultivation
Keywords: Enriquecimento; EDDHA; NFT; Hidroponia; Verão; Enrichment; Hydroponics; Summer; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA